DEVELOPMENT OF NEW TYPES OF SWEET SAUCES WITH DIETARY ADDITIVES - ANTONENKO АRTEM; BAL-PRYLYPKO, LARYSA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article investigates the possibility of expanding the range of sauces based on fruit and vegetable raw materials. The possibility of using pumpkin puree, apple juice, gum arabic, eggplant powder and calcium lactate has been theoretically and experimentally proven. It was found that stewing is the most effective method of heat treatment of pumpkin for use in sauces. The sample obtained by stewing reached the maximum content of reducing sugars (5.5%) already 20 minutes after the start of processing, which indicates faster cooking compared to steaming and baking (40 minutes). The organoleptic evaluation confirmed the advantage of stewing: pumpkin puree obtained by this method received the highest score - 24.4 out of 25, which indicates better taste and texture characteristics compared to other methods. Replacing part of the sugar (up to 60%) with pumpkin puree and apple juice allowed to reduce the energy value of sauces, which is important for creating functional products. Pumpkin puree, which has a lower calorie content compared to sugar, together with apple juice contributed to a decrease in the thickness of the sauce, which improved its rheological properties. Optimal replacement of 60% of sugar with pumpkin puree with the addition of 60% of apple juice from the amount of puree provided a liquid, homogeneous consistency, which makes the sauce convenient for decorating dishes, avoiding excessive thickness as in the control apricot sauce. It was found that the addition of gum arabic (5%), eggplant powder (3%) and calcium lactate (1%) allowed to achieve a stable consistency without the use of starch. Organoleptic evaluation showed that the apricot sauce with pumpkin puree and apple juice has a pleasant sweet and sour taste with notes of apricot and apple, as well as a homogeneous liquid consistency, which is an improvement compared to the control sample. The acidity study showed that the addition of pumpkin puree slightly increased the acidity (maximum 0.432% at 80% replacement), but this did not negatively affect the quality of the sauce, remaining within the acceptable error. The dry matter content decreased from 40.9% in the control sample to 39.9% at 70% apple juice, which contributes to a decrease in density and an improvement in consistency.